Function and clinical meaningfulness of treatments for mild Alzheimer's disease - Siemers, Eric (Alzheimers Dement (Amst), 2016)
INTRODUCTION: Effectiveness of Alzheimer's disease (AD) treatments is commonly evaluated with coprimary outcomes; cognition with function to ensure clinical meaningfulness of a cognitive effect. METHODS: We reviewed the literature for functional outcomes in mild AD or mild cognitive impairment (MCI) patients (distinct from combined mild-moderate/severe AD) treated with approved AD drugs. Cognitive and functional treatment differences in mild AD patients in solanezumab EXPEDITION/EXPEDITION2 studies were compared across time. RESULTS: Seven publications provided MCI/mild AD functional outcomes, one of which reported a significant functional treatment effect. Secondary analyses of EXPEDITION studies suggested a smaller functional effect of solanezumab relative to cognition. An increasing effect of solanezumab over 18 months was shown for cognition and function. DISCUSSION: Function as the sole measure to demonstrate clinical meaningfulness of cognitive effects in mild AD may have limitations. For disease-modifying treatments, point differences on cognitive and functional scales should be qualified with duration of treatment.